Managing Digital Adaptation in Islamic Education While Preserving Aswaja Values - Eli Yanti Manurung; Amiruddin Siahaan; Muhammad Fadhli (Journal of Social Work and Science Education, 2027)
Traditional Islamic educational institutions face the challenge of adapting to digital technology without compromising their religious and cultural identity. This study examines how Pondok Pesantren Darul Qur’an in Medan, Indonesia, manages digital integration while preserving Ahlussunnah wal Jama’ah (Aswaja) values. Employing a descriptive qualitative case study approach, data were collected through passive observation, semi-structured interviews with key stakeholders (head of madrasah, teachers, administrative staff), and document analysis. The findings reveal three main strategies: (1) a “Guided Innovation” model integrating technology as an ideological filter, combining strict digital access control with classical Islamic literacy to maintain Aswaja principles; (2) preservation of the ta’dzim (respect) culture through hybrid-traditional learning methods, though students exhibited behavioral shifts when outside the pesantren environment, indicating the need for deeper internalization of digital ethics; and (3) structured administrative policies, including Standard Operating Procedures, digital skills training, and equitable access programs, effectively bridged the digital literacy gap among students from diverse geographical backgrounds. This study contributes to understanding how traditional Islamic institutions can undergo digital transformation while maintaining their spiritual identity through visionary leadership, systematic management, and value-based adaptation. The findings offer practical insights for Islamic educational institutions navigating the tension between modernization and tradition.